2018
DOI: 10.1103/physrevlett.120.204503
|View full text |Cite
|
Sign up to set email alerts
|

Universal Rim Thickness in Unsteady Sheet Fragmentation

Abstract: Unsteady fragmentation of a fluid bulk into droplets is important for epidemiology as it governs the transport of pathogens from sneezes and coughs, or from contaminated crops in agriculture. It is also ubiquitous in industrial processes such as paint, coating, and combustion. Unsteady fragmentation is distinct from steady fragmentation on which most theoretical efforts have been focused thus far. We address this gap by studying a canonical unsteady fragmentation process: the breakup from a drop impact on a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 48 publications
11
112
2
Order By: Relevance
“…During processes such as gas evolution during electrochemical reactions and boiling, nucleated bubbles grow by mass transfer across the interface [15,16] or coalescence [8], but once the bubble detaches it may deform as it rises up and/or interacts with other bubbles [53]. Other complex processes, such as splashing, involve droplet spreading on a surface which is accompanied by formation of secondary smaller droplets at the rim [81]. To reliably model these processes, surface tension models must be able to accurately handle flow scenarios with both small and large capillary numbers.…”
Section: Publication Remarksmentioning
confidence: 99%
“…During processes such as gas evolution during electrochemical reactions and boiling, nucleated bubbles grow by mass transfer across the interface [15,16] or coalescence [8], but once the bubble detaches it may deform as it rises up and/or interacts with other bubbles [53]. Other complex processes, such as splashing, involve droplet spreading on a surface which is accompanied by formation of secondary smaller droplets at the rim [81]. To reliably model these processes, surface tension models must be able to accurately handle flow scenarios with both small and large capillary numbers.…”
Section: Publication Remarksmentioning
confidence: 99%
“…To better understand the temporal and spatial distribution of the tin mass, we again revisit studies of droplet impact on a pillar [16][17][18]20,26] or on a solid substrate [27,29]. In these studies, the Weber number We = ρ U 2 R 0 /σ is the pertinent parameter to describe the expansion dynamics.…”
Section: Mass Distribution During Sheet Expansionmentioning
confidence: 99%
“…As discussed above, a bounding rim on the edge of the sheet develops during sheet expansion, which has a volume V rim = π 2 R(t)b 2 /2, where b is the rim diameter. Recently, it has been shown that the rim diameter b of an expanding liquid sheet that undergoes unsteady fragmentation is universally governed by a local instantaneous Bond number Bo ≡ −R(t)ρb 2 /σ = 1 [18]. We again refer to Eq.…”
Section: Volume Of the Rim And Fragmentationmentioning
confidence: 99%
See 2 more Smart Citations